2017
DOI: 10.1103/physrevb.96.115422
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-scale shear response of the organic semiconductor β -DBDCS (100) surface

Abstract: In this work we present friction-force microscopy (FFM) lattice-resolved images acquired on the (100) facet of the semiconductor organic oligomer (2Z,2 Z) − 3,3 -(1,4-phenylene)bis(2-(4-butoxyphenyl)acrylonitrile) (β-DBDCS) crystal in water at room temperature. Stick-slip contrast, lateral contact stiffness, and friction forces are found to depend strongly on the sliding direction due to the anisotropic packing of the molecular chains forming the crystal surface along the [010] and [001] directions. The anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The example solute, (2Z,2′Z)-2,2′-(1,4-phenylene)bis(3-(4-butoxyphenyl) acrylonitrile) (DBDCS), is a fluorophore exhibiting aggregation-induced emission. Its fluorescence lifetime and quantum yield increase after aggregation, 22,23 allowing for detection of fluorescent crystal nucleation and growth against a nonfluorescent background. 20,24 DBDCS is insoluble in water (the antisolvent) and slightly soluble in 1,4-dioxane (the "good" solvent, solubility 8 g/L).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The example solute, (2Z,2′Z)-2,2′-(1,4-phenylene)bis(3-(4-butoxyphenyl) acrylonitrile) (DBDCS), is a fluorophore exhibiting aggregation-induced emission. Its fluorescence lifetime and quantum yield increase after aggregation, 22,23 allowing for detection of fluorescent crystal nucleation and growth against a nonfluorescent background. 20,24 DBDCS is insoluble in water (the antisolvent) and slightly soluble in 1,4-dioxane (the "good" solvent, solubility 8 g/L).…”
Section: Introductionmentioning
confidence: 99%
“…The example solute, (2 Z ,2′ Z )-2,2′-(1,4-phenylene)­bis­(3-(4-butoxyphenyl) acrylonitrile) (DBDCS), is a fluorophore exhibiting aggregation-induced emission. Its fluorescence lifetime and quantum yield increase after aggregation, , allowing for detection of fluorescent crystal nucleation and growth against a nonfluorescent background. , DBDCS is insoluble in water (the antisolvent) and slightly soluble in 1,4-dioxane (the “good” solvent, solubility 8 g/L) . Two polymorphs of DBDCS have been reported to switch under shear stress: the γ phase (green emission, fluorescence lifetime >10 ns) and the β phase (blue emission, fluorescence lifetime <6 ns). , The Jouyban–Acree model , allowed us to extract thermodynamic parameters from solubility measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report that the mesoscopic phase transformation can be observed and visualized by friction force microscopy (FFM), an extended technique of static-mode AFM. The FFM detects the torsional response of the AFM cantilever on the sample surface and measures the friction properties of the sample. As friction properties have been utilized for characterizing phase behaviors in many cases of organic and inorganic materials, FFM has the potential for evaluating the crystalline states of OSC films. It is found in the FFM images of spin-coated films of 2-C8-BTNT that high-friction and low-friction phases are separately formed at a mesoscopic scale during annealing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The example solute, DBDCS ((2 Z ,2′ Z )-2,2′-(1,4-phenylene)­bis­(3-(4-butoxyphenyl) acrylonitrile), Figure ), has been previously investigated in a microfluidic system. , It is insoluble in water (the nonsolvent) but slightly soluble in 1,4-dioxane (the “good” solvent). Its fluorescence depends on the molecular arrangement, , enabling further in situ characterization of the polymorphism and the phase transitions. Two polymorphs of DBDCS have been reported: the γ phase (green emission, fluorescence lifetime >10 ns) and the β phase (blue emission, fluorescence lifetime <6 ns).…”
Section: Introductionmentioning
confidence: 99%